Women Empowerment by Women's Farmer Groups (KWT) in Gandasari Village, Jatiuwung District, Tangerang City - Rizkka Amri Respati; Nunung Nurwati; Muhammad Fedryansyah (Green Publisher Indonesia, 2026)
Women’s empowerment remains a critical issue in Indonesia, particularly in urban areas where poverty, gender inequality, and limited economic opportunities continue to restrict women’s participation in productive sectors. In Tangerang City, women’s labor force participation remains significantly lower than that of men, and many women are still concentrated in informal employment. In response to these challenges, the Women Farmers Group (Kelompok Wanita Tani/KWT) has emerged as a community-based initiative promoting women’s empowerment through urban farming activities. This study aims to analyze the process of women’s empowerment implemented by KWT Gemas Implant in Gandasari Village, Jatiuwung District, Tangerang City. The research employed a qualitative approach using Charles Zastrow’s empowerment framework, which consists of engagement, assessment, intervention, and evaluation stages. Data were collected through observations, in-depth interviews, documentation studies, and literature reviews involving extension officers, local government representatives, KWT administrators, and members. The findings indicate that the empowerment process has successfully enhanced women’s participation, self-confidence, agricultural knowledge, and economic independence. KWT Gemas Implant has also strengthened social solidarity, expanded community networks, and promoted the adoption of urban farming technologies. However, several challenges remain, including limited technological utilization, administrative management constraints, environmental issues, and insufficient youth regeneration. Overall, the study concludes that KWT plays a significant role in empowering women and improving community welfare, although sustained institutional support, capacity-building programs, and technological innovation are necessary to ensure long-term sustainability and effectiveness.